Assessment of the Thermal Shock Resistance Figures of Merit of Al2W3O12, a Low Thermal Expansion Ceramic. Issue 5 (2nd March 2016) - Prisco, Luciana P.; Pontón, Patricia I.; Guamán, Marco V.; Avillez, Roberto R.; Romao, Carl P.; Johnson, Michel B.; White, Mary Anne; Marinkovic, Bojan A.
Abstract : Zero thermal expansion phases from the A 2 M 3 O12 and related thermomiotic (negative thermal expansion) families are natural candidates for applications where high thermal shock resistance is the principal requirement. However, their mechanical properties are largely unknown, as are sintering routes for consolidation into bulk objects. Therefore, a preliminary case study on the effect of microstructure on mechanical strength and thermal shock resistance of Al2 W3 O12 has been performed. All thermal and mechanical properties necessary for calculation of thermal shock resistance figures of merit have been measured experimentally. Tensile strengths were measured by four‐point flexural test and analyzed by the Weibull method. The microstructure of bulk specimens, conventionally pressureless sintered at 1273 K, was coarse‐grained, containing microcracks, and inhomogeneous with respect to density due to the agglomeration of nanoparticles, and led to low tensile strength. Despite this, thermal shock resistance features evaluated for Al2 W3 O12 are encouraging. The Hasselman figure of merit for thermal shock resistance for severe heating conditions of Al2 W3 O12 was 120 K, comparable to sapphire, the state‐of‐the‐art material for some advanced thermal shock resistance applications. This study shows that zero thermal expansion phases from the A 2 M 3 O12 family have potential to be transformed into useful engineering ceramics for thermal shock resistance applications.